2016
DOI: 10.1002/mus.24767
|View full text |Cite
|
Sign up to set email alerts
|

Reproducibility of electromyographic and mechanical parameters of the triceps surae during submaximal and maximal plantar flexions

Abstract: The H-reflex during voluntary contraction of the LG should be considered with caution. Mechanical data on muscle activation level are reproducible. The reproducibility of neuromuscular parameters is sufficient for interventional studies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
18
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(22 citation statements)
references
References 44 publications
(124 reference statements)
4
18
0
Order By: Relevance
“…They observed high to moderate reliability for PF MVC strength, PF maximal EMG activity, VAL, M max and H reflex. The reliability of neuromuscular parameters for PF over a period of two weeks was also reported by Stutzig & Siebert (2016) [ 17 ]. They revealed that a majority of the collected neuromuscular parameters (28 of 34) had moderate (ICC, 0.61–0.80) and substantial (ICC, 0.81–1.00) reliability, which led to the conclusion that these measurements are sufficiently consistent to be used in interventional studies.…”
Section: Introductionsupporting
confidence: 67%
See 2 more Smart Citations
“…They observed high to moderate reliability for PF MVC strength, PF maximal EMG activity, VAL, M max and H reflex. The reliability of neuromuscular parameters for PF over a period of two weeks was also reported by Stutzig & Siebert (2016) [ 17 ]. They revealed that a majority of the collected neuromuscular parameters (28 of 34) had moderate (ICC, 0.61–0.80) and substantial (ICC, 0.81–1.00) reliability, which led to the conclusion that these measurements are sufficiently consistent to be used in interventional studies.…”
Section: Introductionsupporting
confidence: 67%
“…The reliability between experimental sessions of PF neuromuscular tests has been previously investigated in the literature for some experimental approaches [ 11 17 ]. Clark et al (2007) [ 11 ] evaluated the reliability of a large number of PF neuromuscular measurements separated by a relatively long duration of time (4 weeks).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The reliability was lower for the MG, which may have contributed to the lack of BOLD differences between age groups. This may be explained by the ability to reliably recruit the MG. MG recruitment was reported to be lower during maximal effort compared to the SOL (7, 38). The ankle position, highly plantar flexed, may have also played a role as this is not the optimal angle for peak PF force.…”
Section: Discussionmentioning
confidence: 99%
“…However, it is unknown whether the pressure applied on the stimulation electrode influences the evoked potentials and the pain experienced by subjects. This methodological issue was rarely mentioned, suggesting that the investigators did not apply pressure on the stimulation electrode while eliciting the evoked potentials (Oya et al ., ; Pinar et al ., ; Tsuruike et al ., ; Behrens et al ., ; Mezzarane et al ., ; Stutzig & Siebert, ,b). In some studies, although pressure on the stimulation electrode was applied using adhesive tape and/or straps (Capaday & Stein, ; Duclay & Martin, ; Sefton et al ., ; Querry et al ., ; Cattagni et al ., ; Baudry et al ., ), the physiological rationale behind this manipulation was not specified.…”
Section: Introductionmentioning
confidence: 99%